1987
DOI: 10.1002/chin.198712206
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Substituted 2‐(2‐Oxobenzopyran‐3‐yl)indoles.

Abstract: Title compounds of type (IV) and (VI) are prepared starting from the reaction between the benzopyran (I) and the anilines (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sinnur et al 48 reported a short and efficient synthesis for aminomethyl-3-coumarinyl ketone hydrochloride 4 via refluxing 3-(bromoacetyl)coumarin 1 with hexamethylenetetramine 3 in drops of concentrated hydrochloric acid ( Scheme 2 ).…”
Section: Reactionsmentioning
confidence: 99%
“…Sinnur et al 48 reported a short and efficient synthesis for aminomethyl-3-coumarinyl ketone hydrochloride 4 via refluxing 3-(bromoacetyl)coumarin 1 with hexamethylenetetramine 3 in drops of concentrated hydrochloric acid ( Scheme 2 ).…”
Section: Reactionsmentioning
confidence: 99%
“…Moreover, bromoacetylcoumarin 2 was reacted with phenylthiosemicarbazide 52 in the presence of pyridine to give 3-(2-phenylamino)-6H-1,3,4thiadiazin-5-yl)-2H-chromen-2-one 53 (Scheme 11). 37 The exocyclic N in compound 53 was acetylated by acetic anhydride to obtain the corresponding N- (5-(2- 40 3-Bromoacetylcoumarin 2, following Bischler's procedure, was reacted with primary aromatic amines, i.e. aniline 65 in ethanol for 15-45 minutes to yield 3-(2-(phenylamino)acetyl)-2H-chromen-2one 66 30 , which was condensed with the respective primary aromatic amine in the presence of catalytic amounts of the amine hydrobromide to give 3-(1H-indol-3-yl)-2H-chromen-2-one 67 (Scheme 13).…”
Section: Scheme 6 Synthesis Of Probe 24mentioning
confidence: 99%
“…The indole structure represents a highly relevant heterocyclic system, since numerous indole‐containing natural and synthetic products such as reserpine, vincristine, indolmicine, mitomycine, pindolol, dolasetron mesylate, indomethacin, or sumatriptan are being used for the treatment of various illnesses. More specifically, several reports describe that indole‐2‐carbohydrazides and related compounds exhibit antihistaminic , antidepressant , MAO inhibitory , and antimicrobial activity . In addition, it was reported that various three‐substituted indoles had been used as starting materials for the synthesis of a number of alkaloids, agrochemicals, pharmaceuticals, and perfumes .…”
Section: Introductionmentioning
confidence: 99%